Alcohol, drinking pattern and all-cause, cardiovascular and alcohol-related mortality in Eastern Europe - Bobak, Martin; Malyutina, Sofia; Horvat, Pia; Pajak, Andrzej; Tamosiunas, Abdonas; Kubinova, Ruzena; Simonova, Galina; Topor-Madry, Roman; Peasey, Anne; Pikhart, Hynek; Marmot, Michael G (European journal of epidemiology, 2016)
Alcohol has been implicated in the high mortality in Central and Eastern Europe but the magnitude of its effect, and whether it is due to regular high intake or episodic binge drinking remain unclear. The aim of this paper was to estimate the contribution of alcohol to mortality in four Central and Eastern European countries. We used data from the Health, Alcohol and Psychosocial factors in Eastern Europe is a prospective multi-centre cohort study in Novosibirsk (Russia), Krakow (Poland), Kaunas (Lithuania) and six Czech towns. Random population samples of 34,304 men and women aged 45-69 years in 2002-2005 were followed up for a median 7 years. Drinking volume, frequency and pattern were estimated from the graduated frequency questionnaire. Deaths were ascertained using mortality registers. In 230,246 person-years of follow-up, 2895 participants died from all causes, 1222 from cardiovascular diseases (CVD), 672 from coronary heart disease (CHD) and 489 from pre-defined alcohol-related causes (ARD). In fully-adjusted models, abstainers had 30-50% increased mortality risk compared to light-to-moderate drinkers. Adjusted hazard ratios (HR) in men drinking on average ≥60 g of ethanol/day (3% of men) were 1.23 (95% CI 0.95-1.59) for all-cause, 1.38 (0.95-2.02) for CVD, 1.64 (1.02-2.64) for CHD and 2.03 (1.28-3.23) for ARD mortality. Corresponding HRs in women drinking on average ≥20 g/day (2% of women) were 1.92 (1.25-2.93), 1.74 (0.76-3.99), 1.39 (0.34-5.76) and 3.00 (1.26-7.10). Binge drinking increased ARD mortality in men only. Mortality was associated with high average alcohol intake but not binge drinking, except for ARD in men.
Keywords: Europe, Eastern; proporcionální rizikové modely; hodnocení rizik; Alcoholism; Male; kohortové studie; Risk Assessment; Risk Factors; Cohort Studies; alkoholismus; Binge Drinking; Mortality; Proportional Hazards Models; otrava alkoholem; Adult; příčina smrti; Aged; dospělí; Alcohol; mužské pohlaví; senioři; Time Factors; kardiovaskulární nemoci; lidé; ženské pohlaví; Humans; Cardiovascular diseases; časové faktory; rizikové faktory; východní Evropa; pití alkoholu; Alcohol Drinking; Alcoholic Intoxication; Cardiovascular Diseases; Eastern Europe; nárazové pití alkoholu; Female; lidé středního věku; Cause of Death; Middle Aged